Regional and cellular distribution of monocarboxylate transporters 13 and 14 in the cattle gastrointestinal tract - Kirat, D; Miyasho, T (Cellular and Molecular Biology, 2015)
Understanding of the basic function of orphan transporters can only be achieved by examining their cellular location. This study is the first to describe the precise cellular localization of the orphan monocarboxylate transporters (MCT13) and (MCT14) in the physiologically distinct regions of the gastrointestinal tract of mammals. The present study demonstrated conclusively the regional distribution and relative expression levels of MCT13 and MCT14 on both mRNA and protein levels in the cattle gastrointestinal tract. The mRNA expression levels of MCT13 and MCT14 in the rumen, abomasum, jejunum, cecum, and proximal colon of cattle were examined using quantitative real time-PCR analysis. The precise cellular location of MCT13 and MCT14 along each part of the cattle stomach and intestine was carried out by immunohistochemistry. The data reveal distinct regional distribution in gene expression profiles of both MCT13 and MCT14 along the cattle gastrointestinal tract. Our study might be beneficial in future research to understand their physiological role in the ruminant gastrointestinal tract.